STRATEGI GURU DALAM MENGENALKAN BAHASA ARAB MELALUI METODE BERMAIN DI TADIKA ALFIKH ORCHARD BANDAR PARKLANDS - Maysarah Maysarah; Hasrian Rudi Setiawan (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
This study aims to describe the strategies used by teachers in introducing Arabic to children through play-based methods at Tadika Alfikh Orchard Bandar Parklands, as well as to identify the types of games used and the supporting and inhibiting factors in their implementation. This study uses a qualitative approach with a descriptive case study type of research. Data collection techniques were carried out through observation of the learning process and in-depth interviews with teachers as the main informants. The data were analyzed using interactive analysis techniques, which included data reduction, data presentation, and conclusion drawing. The results of the study indicate that teachers applying various play-based learning strategies can improve Arabic language comprehension